Cover Image, Volume 11, Issue 2. (18th February 2021) - Seritan, Stefan; Bannwarth, Christoph; Fales, Bryan S.; Hohenstein, Edward G.; Isborn, Christine M.; Kokkila‐Schumacher, Sara I. L.; Li, Xin; Liu, Fang; Luehr, Nathan; Snyder, James W.; Song, Chenchen; Titov, Alexey V.; et al.
Abstract : The cover image is based on the Software Focus TeraChem: A graphical processing unit‐accelerated electronic structure package for large‐scale ab initio molecular dynamics by Stefan Seritan et al., https://doi.org/10.1002/wcms.1494 .